Agricultural insurance and the World Trade Organization - Glauber, Joseph W. (International Food Policy Research Institute, 2015)
This paper examines how agricultural insurance programs are treated under the World Trade Organization (WTO). Agricultural insurance programs have grown considerably over the past 25 years and now are an integral part of many domestic support programs, not just in developed countries, but in important emerging markets as well. An often-cited impetus for the growth in insurance program is the potential treatment of such programs as exempt from WTO reduction commitments. Under Annex 2 of the Uruguay Round Agreement on Agriculture, domestic support measures that have, at most, a minimal impact on trade, so-called green box policies, are excluded from reduction commitments. Yet while WTO rules shield green box policies from reduction, few developed countries have notified agricultural insurance policies under Annex 2. Moreover, crop insurance programs have been challenged in recent WTO dispute settlement cases and domestic countervailing duty investigations.